Renal Transplantation in Patients With Tuberculosis: A Single-center Experience From an Endemic Region - Ashwini B. Gadde, MD, DNB; Pranaw Kumar Jha, MD, DNB; Shyam B. Bansal, MD, DM; Abhyudaysingh Rana, MD, DNB; Manish Jain, MD, DM; Dinesh Bansal, MD, DM; Dinesh Kumar Yadav, MD, DM; Amit Kumar Mahapatra, MD, DM; Sidharth Kumar Sethi, MD, FASN; Vijay Kher, MD, DM (Transplantation Direct, 2023)
Background. Despite being a common infection in end-stage kidney disease patients, there are no evidence-based guidelines to suggest the ideal time of transplantation in patients on antitubercular therapy (ATT). This study aimed to examine the outcome of transplantation in patients while on ATT compared with those without tuberculosis (TB). Methods. This was a retrospective study. Renal transplant recipients transplanted while on ATT were compared with a 1:1 matched group (for age, sex, diabetic status, and type of induction agent) of patients without TB at the time of transplant. Patient outcomes included relapse of TB and graft and patient survival. Results. There were 71 patients in each group. The mean duration for which ATT was given pretransplant was 3.8 ± 2.47 mo. The average total duration of ATT received was 12.27 ± 1.25 mo. Mortality in both the groups was similar (8.4% in the TB group versus 4.5% in the non-TB group; P = 0.49). None of the surviving patients had recurrence of TB during the follow-up. Death-censored graft survival (98.5% in the TB group versus 97% in the non-TB group; P = 1) and biopsy-proven acute rejection rates (9.86% in the TB group versus 8.45% in the non-TB group; P = 1) were also similar in both the groups. Conclusions. Successful transplantation in patients with end-stage kidney disease on ATT is possible without any deleterious effect on patient and graft survival and no risk of disease recurrence. Multicentric prospective studies are needed.